Um método interativo para análise de não-linearidade geométrica em estruturas reticulares - Mantilla, Enrique Paillié (1974)
An iteration procedure is presented to determine the buckling loads of plane and space framed structures taking into account non-linear behavior. Two effects are included in the analysis: the axial forces on the member stiffness matrix and the changes of geometry caused by large displacements. A computer program writed in FORTRAN II is presented and numerical examples are included to illustrate the application.